Micropropagação de duas espécies de veloziaceae da Chapada Diamantina - Pinto, Dinah Ise Jimenez Gonçalves e Costa (2021)
Velloziaceae is one of the main families of the floristic composition of the rupestrian fields of Chapada Diamantina and has species with significant ornamental potential and resistance to climate change. The species Vellozia seubertiana and Vellozia pyrantha stand out for the beauty of the flowers and lack studies to guarantee their propagation and conservation. This work had as objective to establish protocols of micropropagation of the species V. seubertiana and V. pyrantha. For establishment in vitro the seeds of the two species were disinfected and inoculated in MS medium with half the saline concentrations and activated charcoal 1 g L-¹. Whole germinated plants in vitro were used for the induction of shoots in MS ½ medium supplemented with BAP (0.00; 4.44; 8.88 and 17.76 µM) and ANA (0.00 and 2 .22 µM). For V. seubertiana the influence of the consistency of the cultivation medium (solid and liquid) in the multiplication stepwas tested. Shoots of V. seubertiana were inoculated in MS ½ medium containing activated charcoal (0.0 and 1.0 g L-¹) and IBA (0.00 and 2.22 µM) for rooting. Rooted Microplantas had been aclimatized in vegetation house. It was obtained, via direct organogenesis, an average of 5.7 sprouts of V. seubertiana in a medium containing 8.75 µM of BAP and 2.22 µM of ANA and 5.5 sprouts per explant for the species V. pyrantha in medium with 4.44 µM of BAP. The solid medium was more efficient for the multiplication of V. seubertiana. In the rooting phase of V. seubertiana, the presence of activated carbon provided greater growth of the aerial part and root. ex vitro. It is concluded that micropropagation is a promising technique for the species V. seubertiana and V. pyrantha.